Exploring PTDH–P450BM3 Variants for the Synthesis of Drug Metabolites. (17th January 2018) - Beyer, Nina; Kulig, Justyna K.; Fraaije, Marco W.; Hayes, Martin A.; Janssen, Dick B.
Abstract: The conversion of a series of pharmaceutical compounds was examined with three variants of cytochrome P450BM3 fused to phosphite dehydrogenase (PTDH) to enable cofactor recycling. Conditions for enzyme production were optimized, and the purified PTDH–P450BM3 variants were tested against 32 commercial drugs by using rapid UPLC–MS analysis. The sets of mutations (R47L/F87V/L188Q and R47L/F87V/L188Q/E267V/G415S) improved conversion for all compounds, and a variety of products were detected. Product analysis showed that reaction types included C‐hydroxylation, N‐oxidation, demethylation, and aromatization. Interestingly, enzymatic aromatization could occur independent of the addition of reducing coenzyme. These results identified new conversions catalyzed by P450BM3 variants and showed that a small set of mutations in the oxygenase domain could broaden both substrate range and reaction type. Abstract : Putting up P450 by phosphite : The bifunctional fusion enzyme phosphite dehydrogenase–P450BM3 is a good system not only for the conversion of model compounds but also for the discovery of novel activities related to metabolism of human drugs, offering a potentially cost‐effective system for use in high‐throughput and large‐scale applications.